Nova associacao de charcos temporários mediterrânicos do SW da Península Ibérica: Eryngio corniculati-Isoetetum setacei - Silva, Vasco; Molina, José Antonio; Costa, José Carlos; Pinto-Cruz, Carla; Espírito-Santo, María Dalila (Acta Botanica Malacitana, 2009)
New association of Mediterranean Temporary Ponds from the SW of the Iberian Peninsula: Eryngio corniculati-Isoetetum setacei Palavras-chave. Isoeto-Nanojuncetea, Vegetação anfíbia, Rede Natura 2000, Alentejo. Key words. Isoeto-Nanojuncetea, Amphibious vegetation, Natura 2000 Network, Alentejo.